Qualitative Analysis Of The Relationship Between Brand Awareness And Medan City Public Preferences For Momoyo Products - Ekry Syahriwanda; Chuzaimah Batubara; Khairina Tambunan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study was to evaluate the level of brand awareness of Momoyo products among Medan City residents. This study measures consumer familiarity and memory of Momoyo products using four main indicators: top of mind, brand recall, brand recognition, and brand ignorance. A qualitative approach with descriptive methodology was used in this study. Data collection was conducted through semi-structured in-depth interviews and supported by documentation. The research subjects consisted of Medan City residents who were selected as informants. The data analysis process was carried out through several stages: data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that Momoyo products have achieved a satisfactory level of brand awareness among Medan City residents.